Religious and cultural aspects of Arab and Kazakh ethics (Journal of Oriental Studies, 2016)
This article critically reviews the existing and, in some cases, contradictory research on cultural communication patterns in the Arab and Kazakh countries. It then reviews recent investigations of Arab cultural communication patterns from an interdisciplinary perspective. More specifi cally, it focuses on several themes as basic cultural values, etiquette formulas of politeness which is need to successful communication in Kazakh and Arab societies. Following each theme are directions for future research. Finally, the article proposes strategies to overcome barriers to new views in intercultural communication and translation studies.